Modelling of billet shapes in spray forming using a scanning atomizer - Kang, Shinill; Chang, Dong-Hoon (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 1999)
A numerical method is presented to predict and analyze the shape of a growing billet produced from the ‘spray forming’ which is a fairly new near-net shape manufacturing process. It is important to understand the mechanism of billet growth because one can obtain a billet with the desired final shape without secondary operations by accurate control of the process, and it can also serve as a base for heat transfer and deformation analyses. The shape of a growing billet is determined by the flow rate of the alloy melt, the mode of nozzle scanning which is due to cam profile, the initial position of the spray nozzle, scanning angle, and the withdrawal speed of the substrate. In the present study, a theoretical model was first established to predict the shape of the billet and next the effects of the most dominant processing conditions, such as withdrawal speed of the substrate and the cam profile, on the shape of the growing billet were studied. Process conditions were obtained to produce a billet with uniform diameter and flat top surface, and an ASP30 high speed steel billet was manufactured using the same process conditions established from the simulation.